Binary copper and manganese oxide nanoparticle supported OMS-2 for enhancing activity and stability toward CO oxidation reaction at low temperature - Nguyen Trung Thanh; Anh, Nguyen Thi Quynh (Vietnam Journal of Science and Technology, 2018)
The CuO, CuMnOx and MnOx catalysts were anchored on the manganese oxide support with the structure of octahedral molecular sieves (OMS-2), which were synthesized using MnSO4 and KMnO4 as precursors by are flux method under acidic conditions, by an impregnation method and tested for CO oxidation. These catalysts and OMS-2 support were characterized by the advanced analyzations of X-ray diffraction and FTIR patterns; and SEM performances; and H2-TPR profiles. For CO oxidation reaction, CuO and CuMnOx catalysts showed extremely higher activities than that of MnOx catalyst and OMS-2 support. For the lowest temperature for 100% conversion of CO (T100), the CuO and CuMnOx catalysts were observed at 55 oC and 65 oC, respectively. Due to the present of Cu2+– O2− – Mn4+ ↔ Cu+–□–Mn3+ + O2 redox couple in the structure of these solid catalyst. Additionally, the CuMnOx catalyst showed higher activity ( 1.74 folds) and better stability than that of CuO catalyst in CO oxidation. Due to the advance functional of binary oxide structure of CuMnOx catalyst As known, CO oxidation may follow the Mars-van-Krevelen mechanism with Cu2+– O2− – Mn4+ ↔ Cu+–□–Mn3+ + O2 redox couple. This study shows the high applicating potential of CuMnOx/OMS-2 material in exhaust treatment for environmental safety